1994
DOI: 10.1099/00222615-41-2-145
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical differences among human and animal streptococci of Lancefield group C or group G

Abstract: Summary. Pyogenic streptococci of Lancefield group C or group G from human or animal sources were examined with a view to increasing the number of diagnostic tests useful for their differentiation. Human strains of group G produced L-prolyl-L-arginine aminopeptidase but isolates of Streptococcus equisimilis (group C) did not. Tests for a-L-glutamate aminopeptidase together with fermentation of glycogen or sorbitol distinguished S. dysgalactiae from strains of S. equisimilis isolated from animals. It was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 8 publications
4
33
0
Order By: Relevance
“…There was one prevalent biotype among the isolated strains which produced phosphatase, leucine amidopeptidase, arginine dihydrolase, alpha-D-and beta-D-galactosidase and fermented lactose and ribose. Results from the biochemical tests that are typically variable (including pyrrolidonylarylamidase, alpha-D-and beta-D-galactosidase, beta-D-glucuronidase, and acidification of lactose and trehalose) were generally within the range of proportions reported for S. canis by other researchers (Clark et al 1984;Devriese et al 1986;Efstratiou et al 1994;Vieira and Castro 1994;Soedarmanto and Lammler 1996). Only 16.3% of S. canis strains were positive for esculin hydrolysis, which is in contrast to the results of Devriese et al (1986) and Vieira and Castro (1994), who found 100% and 90% of strains positive, respectively.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…There was one prevalent biotype among the isolated strains which produced phosphatase, leucine amidopeptidase, arginine dihydrolase, alpha-D-and beta-D-galactosidase and fermented lactose and ribose. Results from the biochemical tests that are typically variable (including pyrrolidonylarylamidase, alpha-D-and beta-D-galactosidase, beta-D-glucuronidase, and acidification of lactose and trehalose) were generally within the range of proportions reported for S. canis by other researchers (Clark et al 1984;Devriese et al 1986;Efstratiou et al 1994;Vieira and Castro 1994;Soedarmanto and Lammler 1996). Only 16.3% of S. canis strains were positive for esculin hydrolysis, which is in contrast to the results of Devriese et al (1986) and Vieira and Castro (1994), who found 100% and 90% of strains positive, respectively.…”
Section: Resultsmentioning
confidence: 53%
“…Only 16.3% of S. canis strains were positive for esculin hydrolysis, which is in contrast to the results of Devriese et al (1986) and Vieira and Castro (1994), who found 100% and 90% of strains positive, respectively. On the other hand, Efstratiou et al (1994) described only 40% of strains as esculin positive and all positive reactions were reported as delayed, which might be responsible for some of the discrepancy. According to Hassan et al (2005) all S. canis isolates appeared to be esculin negative on primary culture; whereas, the isolates were uniformly positive after they were subcultured.…”
Section: Resultsmentioning
confidence: 84%
“…HhaI, MboII, and Sau3A patterns are quite similar for these three species as well, although DNA homology between species is between 45 and 75% (32) and 16S rRNA similitude value is limited to 96 to 97% (1). However, the classification of this group remained controversial as no test was clearly capable of differentiating these species (9,29,32).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of streptococcal species is currently based on observation of the cultural and morphological characteristics, determination of the biochemical pattern (production of enzymes and production of acid from various carbohydrate sources) (4,5,6,9,11,17,20), and observation of the antigenic structure according to the classification of Rebecca Lancefield (22).…”
mentioning
confidence: 99%
“…A number of biochemical characteristics are known to be useful in differentiating human GGS (S. dysgalactiae subsp. equisimilis) and animal GGS (S. canis), as illustrated in Table 1 (2,3,5,6). The most informative dis-criminatory tests are recognized to be the production of ␣-galactosidase and ␤-galactosidase and the production of acid from trehalose.…”
mentioning
confidence: 99%